Dampak Data Penjualan Kamar dan Sistem Reservasi Online terhadap Efisiensi Operasional Hotel di Kabupaten Gianyar - Gede Indirayanti Kusumaputri, Ida Ayu; Diatmika, I Putu Gede; Martadinata, I Putu Hendra (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study focuses on the study of the influence of room sales data and the use of online reservation systems on improving the operational efficiency of hotels in Gianyar Regency. The analysis was carried out using a quantitative method, using data collected directly from respondents through a questionnaire on a Likert scale of 1-5, involving 211 hotel workers as respondents. Data processing includes descriptive analysis, data quality test, classical assumption test, multiple linear regression, and hypothesis testing with the support of the IBM SPSS Statistics 25 program. The findings of the study indicate that both individually and simultaneously, room sales data and online reservation systems have a positive and significant impact on hotel operational efficiency.